Imunitas dan Kesehatan Tubuh melalui Aktivitas Olahraga yang Efektif - Dony, Garry William; Bernisa, Bernisa; Razzi, Fahrul; Wisman, Yossita (Jurnal Ilmiah Kanderang Tingang, 2025)
Measured and well-planned exercise, along with a balanced nutritional intake, are essential factors in maintaining the body's immunity. Regular physical activity can enhance the function of the heart, lungs, and circulatory system, as well as play a role in preventing diseases such as heart disease, hypertension, and stroke. However, not all types of exercise can be performed by the public, especially during a pandemic. Several factors need to be considered, including accessibility, time efficiency, and the availability of equipment and space. To support immune enhancement, exercise should adhere to the FITT principles (Frequency, Intensity, Time, Type). The recommended frequency of exercise is 3–5 times per week, with a moderate intensity (65%–75% of maximum heart rate). The suggested duration is 20–30 minutes per session, which can be increased up to one hour depending on individual capability. Recommended types of exercise are aerobic activities such as stationary cycling, walking, jogging, or jumping in place. Additionally, exercising in a positive mood can boost endorphin production, contributing to improved immune resilience.